PLACE NAME CHANGES AND THREATS TO CULTURAL PRESERVATION: AN ANTHROPOLINGUISTIC STUDY IN BANTUL REGENCY YOGYAKARTA, INDONESIA - Lia Amrina (Epigram, 2025)
Place-name changes in Bantul Regency, Indonesia, often driven by modernization, administrative interests, or infrastructure development, threaten the preservation of local culture by erasing the historical and cultural values embedded in the original names. This anthropological study aims to analyze the impact of place-name changes on cultural preservation and provide recommendations for protecting traditional names as part of cultural heritage. This study employs a qualitative approach that utilizes primary data from in-depth interviews with community leaders, cultural experts, and local historians, as well as secondary data from literature studies, historical archives, government documents, and local cultural records. Linguistic and anthropological analyses were conducted to identify the meaning and structure of place names before and after the changes and to understand the cultural and historical values they contain. This study reveals that place-name changes in Bantul, such as the merging of villages such as Gandekan, Teruman, and Bedjen into Bantul or the renaming of Ringinharjo to Bantulkarang, can lead to a loss of cultural and historical meaning, erode local identity, and disconnect communities from their heritage. The impact of these changes is complex and interrelated, with both positive and negative consequences for social, administrative, and bureaucratic aspects. This study emphasizes the importance of involving all stakeholders in the process of changing place names to maximize positive impacts and minimize negative ones. This highlights the need to preserve traditional place names as part of cultural heritage through documentation, promotion, and protection efforts by the government and community.